Debt, distress, dispossession: towards a critical political economy of Africa's financial dependency. Issue 171 (2nd January 2022) - Zajontz, Tim
SUMMARY: With China's rise to become Africa's largest bilateral creditor, much research has focused on an evidence-based critique of the politicised narrative about China's supposed 'debt trap diplomacy'. At a more fundamental level, this debate problematises the function of debt and related power differentials in late capitalism and calls into question development paradigms, notably the hegemonic infrastructure-led development regime, that have sustained Africa's financial dependency into the 2020s. As the International Monetary Fund is yet again shuttling between Addis Ababa, Lusaka, and Nairobi to resurrect fiscal discipline and to ensure debtor compliance for the post-pandemic 'payback period', it is argued that (i) periodic cycles of debt financing, debt distress and structural adjustment are a systemic feature of the malintegration of Africa into the global capitalist economy, and (ii) critical research on the social costs and economic beneficiaries of renewed rounds of austerity and privatisation in Africa's current debt cycle is needed.